Effect of Different Production Methods on the Mechanical and Microstructural Properties of Hypereutectic Al-Si Alloys - Kilicaslan, M. Fatih; Uzun, Orhan; Yilmaz, Fikret; Caglar, Seyit (Springer Science and Business Media LLC, 2014)
In this study, the effects of different production methods like melt spinning, high-energy ball milling, and combined melt spinning and high-energy ball milling on the mechanical and microstructural properties of hypereutectic Al-20Si-5Fe alloys were investigated. While microstructural and spectroscopic analyses were performed using scanning electron microscopy and X-ray diffractometry, mechanical properties were measured using a depth-sensing indentation instrument with a Berkovich tip. Microstructural and spectroscopic analyses demonstrate that high-energy ball milling process applied on the melt-spun Al-20-Si-5Fe alloy for 10 minutes brings about a reduction in the size of silicon particles and intermetallic compounds. However, further increase in milling time does not yield any significant reduction in size. High-energy ball milling for 10 minutes on the starting powders is not enough to form any intermetallic phase. According to the depth-sensing indentation experiments, high-energy milling of melt-spun Al-20Si-5Fe alloys shows an incremental behavior in terms of hardness values. For the Al-20Si-5Fe alloys investigated in this study, the production technique remarkably influences their elastic–plastic response to the indentation process in terms of both magnitude and shape of P-h curves.
Keywords: nano-technology; physical sciences; natural sciences; hızlı katılaştırma, alaşımlama, makanik alaşımlama; Good health; engineering and technology; Economic growth; 8. Economic growth; 3. Good health